The impact of delaying early school tracking on fertility and marriage outcomes - Serena Canaan (W.E. Upjohn Institute for Employment Research, 2024)
This paper studies how the type of education pursued at an early age affects family formation. I focus on a French reform that delayed the age of which students were tracked into either general or vocational education from age 11 to age 13. For the most part, tracking was replaced with grouping students into classrooms based on ability, but within a common general education curriculum. Using a regression discontinuity design, I show that the reform increased the likelihood of attaining a technical rather than a vocational degree, especially for individuals from low socioeconomic backgrounds. This indicates that the reform led to an increase in the quality of education. I further find that the reform increased completed fertility for individuals from low socioeconomic backgrounds, particularly women. In the marriage market, the reform changed the characteristics of women's partners without impacting marriage, cohabitation, or divorce rates. Specifically, women were more likely to have partners who were in high-skilled occupations and who were closer to their own ages. Taken together, these findings highlight that delaying early school tracking has significant consequences for family formation.
Keywords: I21; I28; J24; 330; tracking; returns to education; fertility; marriage